2017
DOI: 10.1021/acssuschemeng.7b03586
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Lignin S/G Ratio in Biomass Recalcitrance of Populus trichocarpa Variants for Bioethanol Production

Abstract: Lignin S/G ratio has been investigated as an important factor in biomass recalcitrance to bioethanol production. Because of the complexity and variety of biomass, recalcitrance was also reportedly influenced by several other factors, such as total lignin content, degree of cellulose polymerization, etc. In addition, the effect of S/G ratio on biomass conversion is not uniform across plant species. Herein, 11 Populus trichocarpa natural variants grown under the same conditions with similar total lignin content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 38 publications
6
78
3
Order By: Relevance
“…The importance of the S/G ratio has been reported in prior work with various Populus species and ratios of such previous work are included in Table 1. While other work has highlighted the significance of the S/G ratio of lignin [5,23,32], no such a correlation of S/G to recalcitrance was noted with the microbial-based assay utilized in this study.…”
Section: Analysis Of Fermentation Productscontrasting
confidence: 70%
See 2 more Smart Citations
“…The importance of the S/G ratio has been reported in prior work with various Populus species and ratios of such previous work are included in Table 1. While other work has highlighted the significance of the S/G ratio of lignin [5,23,32], no such a correlation of S/G to recalcitrance was noted with the microbial-based assay utilized in this study.…”
Section: Analysis Of Fermentation Productscontrasting
confidence: 70%
“…While the overall lignin content negatively correlated to the yield of fermentation products, the type of lignin present can also affect the recalcitrance of the lignocellulosic feedstock. A higher ratio of syringyl to guaiacol subunits (S/G ratio) present in the lignin has previously been suggested to improve the saccharification yield of P. trichocarpa and subsequent ethanol yield from fermentation of the enzymatically saccharified biomass with yeast [32]. For the lines tested here with available data on S/G ratio, the higher ratios correlated weakly with increased fermentation performance (R 2 = 0.41) (Fig.…”
Section: Analysis Of Fermentation Productsmentioning
confidence: 57%
See 1 more Smart Citation
“…However, the correlation between lignin S/G ratio and recalcitrance is still not obvious. For example, Herbaut et al and Yu et al showed a positive correlation between the S/G ratio and the hydrolysis yields for miscanthus and woody chips (Yu et al, 2014;Herbaut et al, 2018) because of the higher binding capacity of G (with branched structure) over S (with linear structure and low degree of polymerisation) to cellulase (Guo et al, 2014;Yoo et al, 2017b). By contrast, others found a negative correlation between S/G ratio and the enzymatic hydrolysis in woody chips (Papa et al, 2012), in pretreated miscanthus (Xu et al, 2012;, in pre-treated wheat straw (Jiang et al, 2016) and in genetically engineering poplar (Escamez et al, 2017).…”
Section: Ligninmentioning
confidence: 99%
“…The molecular composition and structure of lignin plays an important role for biomass recalcitrance and subsequently lignin valorization [26,43]. In particular, the role of S/G ratio for recalcitrance has been intensively studied [48,49].…”
Section: Multivariate Data Analysismentioning
confidence: 99%